Types of Flouting Maxims analysis in Jurassic World Dominion Movie - Putri Melania; Afriana Afriana (LPPM Universitas Bumigora Mataram, 2023)
Flouting maxims present as pragmatics phenomena that can be easily found in society. It comes in the communication that does not obey the cooperative principles. In this research, flouting maxims in utterances uttered by characters of movie was analyzed. The types of flouting maxims became the object of this research. The researchers used Jurassic World Dominion movie to be the data source of this descriptive qualitative research. Flouting maxims utterances were collected as data and those were analyzed by using the theory of Grice (1975). Observational method and technique of non-participatory were used to collect the flouting maxims utterances. In analyzing the data, the researchers applied pragmatic identity method and pragmatic competence- in equalizing technique. The results showed that there were 15 data found in Jurassic World Dominion movie. The 15 data consisted of 7 data of flouting maxim of relation , 3 data of flouting maxim of quality, 3 data of flouting maxim of quantity, and 2 data for maxim of manner